Unemployment and Social Disorder during the British Colonial Period in Eritrea (1941–1951) - Beyan, Temesgen Tesfamariam (Aethiopica, 2020)
This article investigates the connection between unemployment and social disorder that characterized British colonial rule in Eritrea between 1941 and 1951. Using the archives of labour of the British period, this article documents the causes of social disorder that galvanized the British period in Eritrea. Based on archival documents, the article argues that the public insecurity and social disorder of the British period were largely related to socio-economic conditions resulting in mass unemployment caused by (1) the dissolution of the colonial army institution; (2) the destruction of the manufacturing industries; (3) the importation of labour from neighbouring British colonies. Upon the defeat of Italy by the British in Eritrea during WWII, the British system had a clearly diminished appetite for colonialism and abandoned any agenda of capitalist expansion, inflicting massive redundancies on the labour force. This produced new social groups such as migrant workers, brigands, and vagabonds. Based on these archival documents, an alternative explanation is introduced pinpointing far more accurately the sources of public insecurity and social disorder during the British colonial period between 1941 and 1951.